2022
DOI: 10.1159/000524894
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of COVID-19 Vaccination in Melanoma Patients under Immune Checkpoint Blockade

Abstract: <b><i>Background:</i></b> Immunogenicity of SARS-CoV-2 vaccines is modestly impaired in cancer patients due to a generally weakened immune system. Immune checkpoint inhibitors (ICI) are expected to enhance immune response. This has already been described to be the case in influenza vaccines, and first data about COVID-19 vaccines show a trend in this direction. <b><i>Aim:</i></b> We aimed to investigate the immune response of patients with melanoma under ICI ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…On the one hand, comparable antibody responses against COVID-19 vaccination were observed between cancer patients with PD-1/PD-L1 ICB therapy and healthy participates [44] , [45] , which hints the restoration of tumor-blunted COVID-19 vaccine effectiveness in patients receiving PD-1/PD-L1 ICB therapy to that of healthy participates. Indeed, cancer patients with PD-1/PD-L1 ICB therapy showed a trend towards increased COVID-19 vaccine effectiveness as compared to that of cancer patients with no therapies [5] , [46] . Otherwise, several studies reported lower COVID-19 vaccine-induced antibody responses in cancer patients receiving PD-1/PD-L1 ICB therapy relative to healthy participants [47] , [48] .…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, comparable antibody responses against COVID-19 vaccination were observed between cancer patients with PD-1/PD-L1 ICB therapy and healthy participates [44] , [45] , which hints the restoration of tumor-blunted COVID-19 vaccine effectiveness in patients receiving PD-1/PD-L1 ICB therapy to that of healthy participates. Indeed, cancer patients with PD-1/PD-L1 ICB therapy showed a trend towards increased COVID-19 vaccine effectiveness as compared to that of cancer patients with no therapies [5] , [46] . Otherwise, several studies reported lower COVID-19 vaccine-induced antibody responses in cancer patients receiving PD-1/PD-L1 ICB therapy relative to healthy participants [47] , [48] .…”
Section: Discussionmentioning
confidence: 99%
“…108 Melanoma patients receiving ICI therapy showed comparable antibody responses after COVID-19 vaccination. 109 Conversely, with mRNA vaccination for COVID-19, patients with lung cancer who received ICI treatment did not have an increased incidence of irAEs. 110,111 Consensus recommendation 10 For cancer patients, it is necessary to decide whether vaccination is appropriate based on various parameters, such as disease severity, treatment stage, and treatment methods.…”
Section: Vaccinated Patientsmentioning
confidence: 98%
“… 108 Melanoma patients receiving ICI therapy showed comparable antibody responses after COVID-19 vaccination. 109 Conversely, with mRNA vaccination for COVID-19, patients with lung cancer who received ICI treatment did not have an increased incidence of irAEs. 110 , 111 …”
Section: Administration Of Icis To Special Populationsmentioning
confidence: 98%
“…They also observed a tendency for higher antibody levels when ICI therapy was received within the last six months before vaccination. Moreover, subgroup analysis revealed that patients under ongoing targeted therapy during the vaccination period had significantly higher median antibody levels than patients without any active antitumor treatment [91].…”
Section: Icis and Anti-infectious Vaccinesmentioning
confidence: 99%